Improving Students' Critical Thinking Skills Using E-booklet Learning Media on Environmental Pollution Material - Meriza, Nadya; Yolida, Berti; Marpaung,, Rini Rita T.; Predita, Febri (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
This study aims to determine the effect of using e-booklet media on the critical thinking skills of class VII students of SMP N 1 Way Tenong on environmental pollution. This research is an experimental research using design through pretest posttest quasi nonequivalent control group design experiment. The type of data used is quantitative and qualitative. The population in this study were students of class VII SMP N 1 Way Tenong and 2 classes were taken randomly using a simple random sampling technique. VII D class as the experimental class and VII E class as the control class. Data was collected through test instruments and questionnaires. The test instrument consists of 20 multiple choice questions which are made using four aspects of critical thinking indicators, namely: giving simple explanations, making further explanations, setting strategies, techniques, and concluding. The questionnaire instrument contains questions related to student responses learn using e-booklets. During learning process was performed using an independent sample t-test statistical test. The results of data analysis showed a significance value of 0.000 < 0.05, and the experimental class obtained an average n-gain result of 0.4184 in the medium category, while the control class obtained an average n-gain score of 0.2789 in the low category. The percentage of student response questionnaires obtained an average percentage of 70% in the well received category. This can be said that there is a significant influence of the use of e-booklet media on student’s critical thinking skills on environmental pollution material